Kemiskinan dan Tanggung Jawab Konstitusi Negara - Muh. Khaerul Anas (SIMPUL: Jurnal Ilmu Politik dan Hukum, 2026)
Poverty is a multidimensional problem that is not only related to economic aspects but also encompasses legal, social, and political dimensions. Within the framework of a rule-of-law state and a welfare state, poverty is closely linked to the constitutional responsibility of the state to fulfill the fundamental rights of its citizens. This article aims to analyze poverty as a constitutional issue and to examine the extent of state responsibility in poverty alleviation based on the constitutional framework, particularly the 1945 Constitution of the Republic of Indonesia. This study employs a normative legal research method using statutory and conceptual approaches, conducted through a literature review of legal documents, academic literature, and relevant previous studies. The findings indicate that the Indonesian Constitution explicitly and implicitly imposes obligations on the state to respect, protect, and fulfill economic, social, and cultural rights as the foundation for poverty alleviation. However, the implementation of these responsibilities continues to face structural, institutional, and policy-related challenges. This article concludes that poverty should not be viewed merely as an individual failure, but rather as an indicator of the effectiveness of the state’s constitutional responsibility. Strengthening constitutional commitment, policy consistency, and state accountability constitutes an important implication of this study, both theoretically and practically.